Apropriação cultural da estética negra: práticas discursivas e lutas de representação no ciberespaço - Silva, Talita Brasil e (2018)
This research aims to understand the discussion about cultural appropriation and black aesthetics in the brazilian context and how it is expressed in the articles published by Geledés – Instituto da Mulher Negra, on the cyberspace. These investigations are guided by the attempt to understand the notion of cultural appropriation used in the discussions, indentify agents that operate appropriation practices and constitutive elements of these debates. The research corpus is made of a collection and analysis of eighteen articles published by the Instituto, trying to rebuild the perception about the observed phenomenon. Hence, it is a qualitative research because of it’s goals of exploring discursive practices and meanings shared in each one of the selected articles, identifying the construction of social representations around the idea of cultural appropriation from black aesthetics. The general hypothesis is that the appropriation practices here investigated are associated to the emptying of the original meaning assigned to some afro-brazilian cultural manifestations. This empyting is performed by State’s actions, that converts ethnic elements in national symbols, by market’s action, that turns these elements in exotic goods, and by people’s actions, that rework, among different perceptions, the original meanings of such cultural manifestations. From this, it was inferred that there are conflicts around the legitimacy of meanings assigned to afro-brazilian cultural manifestations, setting representation disputes between the black movements and agents that operate these appropriation practices.